Factors Influencing Pre-Hospital Delay in Acute Coronary Syndrome Patients - Ika Ainur Rofi'ah (Universitas STRADA Indonesia, 2026)
Background: Acute Coronary Syndrome (ACS) is a major cause of morbidity and mortality worldwide, with delayed hospital presentation contributing to poor outcomes. Pre-hospital delay, defined as the time from symptom onset to seeking definitive care, is influenced by patient, symptom, and system-related factors. Evidence from Indonesia on determinants of such delays remains limited. Purpose: This study aimed to analyze factors associated with pre-hospital delay among ACS patients in the Emergency Department of Dr. Wahidin Sudiro Husodo Regional Hospital, Mojokerto City. Methods: An observational, analytic, cross-sectional study was conducted in 2024, with 70 adult ACS patients recruited through consecutive sampling. Data were collected via standardized questionnaires and medical record review, including demographic, clinical, transportation, attack type, symptom onset timing, health insurance, and ACS knowledge. Bivariate and multivariate logistic regression analyses were performed to identify predictors of pre-hospital delay. Results: The mean age of respondents was 61.67 years, with 60% male and 61.4% lacking knowledge of ACS. Most arrived by private vehicle (87.1%) and experienced a new attack (77.1%). Pre-hospital delay occurred in 77.1% of respondents. Multivariate analysis showed that the type of attack had the highest odds ratio (OR = 5.55) for pre-hospital delay, although not statistically significant (p = 0.115). Transportation, time of onset, and ACS knowledge did not demonstrate significant associations but suggested potential confounding effects. Conclusion: Pre-hospital delay is highly prevalent among ACS patients in this setting. No significant predictors were identified, suggesting delays reflect complex behavioral and system factors. Given the limited sample size, the findings should be interpreted with caution. Improving public awareness and emergency access remains essential.